Oseointegración de implantes de titanio en fémur de conejo oseointegration of titanium implants in rabbit femur - Cattaneo U., Gino; Maureira V., Andrés; Flores P., Estefanía; Oróstegui, César; Oyarzún, Alejandro (Avances en Ciencias Veterinarias, 2002)
In order to improve the oseointegration in extreme situations, new elements, forros and dimensions have been looked for as implants. A topic of interest study is the new implant of threaded titanium of different diameters. In the femur of the rabbit it was developed a model to observe and to describe the Oseointegration. Three couples of threaded titanium implants of different diameters (3.75, 4 and 5 mm) and 10 mm long, were placed in the femur of 6 rabbits, giving them a 4 months period of rest. After this period, histological descriptive studies of the bone around the implants were carried out. The formation of compact vital bony tissue stuck to the implant, without presence of inflammatory cells in the crea that could indicate a failure in the oseointegration was observed. A good behavior of the titanium implants, and capacity of the bony tissue to accept and interact with this inert material were observed.